The Effect of Digital Transactions, Interest Rates, and the COVID-19 Pandemic on the Money Supply in Indonesia (2018-2023) - Nur Fadilah, Isnaini; Aditya Dwi Pamungkas; Ara Danisy (Bulletin of Islamic Economics, 2025)
This study analyzes the effect of digital transactions, interest rates, and the COVID-19 pandemic on the money supply (M2) in Indonesia from August 2018 to August 2023. Using monthly time series data from Bank Indonesia, BPS, and Katadata, the research employs multiple linear regression with the Ordinary Least Squares (OLS) method. The results show that digital transactions have a positive and significant effect on the money supply, indicating that the digitalization of financial systems accelerates the circulation of money in the economy. Meanwhile, the benchmark interest rate has no significant direct effect on M2, suggesting that its traditional role in monetary control may be diminishing in the digital era. The COVID-19 pandemic dummy variable shows a positive and significant impact on the money supply, reflecting the effects of fiscal and monetary stimulus policies during the crisis. Overall, the findings highlight that technological transformation and crisis conditions substantially influence liquidity dynamics, and that monetary policy must adapt to digital and structural economic changes.